Nanga merit fishes assemblages and their feeding behaviors - Farah Adibah, Esa. (Universiti Malaysia Sarawak, (UNIMAS), 2010)
This study was conducted to identify the diversity of freshwater fish and their teeding behavior in Nanga Merit. A total of 106 individuals comprising 15 families belonging to 5 families and II genera were caught. Cyprinidae and Siluridae were identified to be the dominant family representing 60.4% and 22.6% respectively. The commonly caught individuals wcr.: from the genera Cyclocheichillys (23.6%), Rasbora (14.2%) and Bm"bodr:s (12.3%). Low number of individuals was obtained during this study most probably due to the effects of poisoning (commercial pesticides and tuba sap) and the low water level during dry season. There three main feeding behavior of fish in Nanga Merit, namely carnivore, herbivore and omnivore. Based on the diet analysis, the major types consumed are diatoms, algae and invertebrates lwonns, nematodes, copepod, rotifer and larvae chironomid). Data obtained during this project serves as baseline data for freshwater fish in Sarawak.